2007
DOI: 10.1029/2005jd006845
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of the influence of a quasi‐2‐day wave on nonlinear photochemical oscillations in the mesopause region

Abstract: [1] The influence of a quasi-2-day atmospheric wave of given amplitude on the 2-day photochemical oscillations occurring in the mesopause region (heights of 80 to 90 km) in the regime of subharmonic nonlinear response to diurnal variations of solar radiation is investigated. It is revealed that the most significant mechanism is periodic transport of minor gas constituents by the vertical wind associated with the wave. This mechanism may lead to phase locking of photochemical oscillations to wind oscillations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Traces of QTDWs can also be found in atmospheric H 2 O, carbon monoxide, OH emission, and height of the F2 layer (Wu et al, 1993;Randel, 1994;Forbes and Zhang, 1997;Limpasuvan and Wu, 2003;Limpasuvan et al, 2005;Tunbridge et al, 2011;Pedatella and Forbes, 2012). Moreover, QTDWs are found to be important in photochemical processes in the mesopause region (Kulikov, 2007). Many studies have suggested that QTDWs can frequently interact with solar tides (Palo et al, 1999;Salby and Callaghan, 2008;McCormack et al, 2010;Babu et al, 2011;Forbes and Moudden, 2012), other PWs (Babu et al, 2011) and gravity waves (GWs) (Palo et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Traces of QTDWs can also be found in atmospheric H 2 O, carbon monoxide, OH emission, and height of the F2 layer (Wu et al, 1993;Randel, 1994;Forbes and Zhang, 1997;Limpasuvan and Wu, 2003;Limpasuvan et al, 2005;Tunbridge et al, 2011;Pedatella and Forbes, 2012). Moreover, QTDWs are found to be important in photochemical processes in the mesopause region (Kulikov, 2007). Many studies have suggested that QTDWs can frequently interact with solar tides (Palo et al, 1999;Salby and Callaghan, 2008;McCormack et al, 2010;Babu et al, 2011;Forbes and Moudden, 2012), other PWs (Babu et al, 2011) and gravity waves (GWs) (Palo et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In the MLT they can reach large amplitudes and are important because they can modulate the amplitude of atmospheric tides (e.g., Teitelbaum and Vial, 1991;Mitchell et al, 1996;Palo et al, 1999;Pancheva et al, 2004), influence the transport and photochemistry of minor species (e.g., Kulikov, 2007), modulate the fluxes of gravitywave momentum that drives the planetary-scale circulation of the upper middle atmosphere (e.g., Forbes et al, 1991;Miyahara and Forbes, 1991;Thayaparan et al, 1995;Nakamura et al, 1997;Manson et al, 2003) and cause perturbations in temperatures that can modulate the occurrence of Polar Mesospheric Clouds (e.g., Espy and Witt, 1996;Merkel et al, 2003Merkel et al, , 2008Nielsen et al, 2010) and Polar Mesospheric Summer Echoes (e.g., Morris et al, 2009). A major component of the planetary-wave field in the MLT is the so-called normal modes that manifest as the 2-, 5-, 10-and 16-day planetary waves (e.g., Salby, 1981a,b).…”
Section: K a Day Et Al: Mean Winds Temperatures And The 16-and 5-dmentioning
confidence: 99%
“…The most prominent planetary wave component in the mesosphere is the quasi-2-day wave (Q2DW) with amplitudes larger than 10 K in temperature and wind amplitudes of several tens of m s −1 in the mid-to low-latitude summer mesosphere (Tunbridge et al, 2011;Wu et al, 1993). The QT2W can interact with atmospheric tides and influence the variability of polar mesospheric clouds (Merkel et al, 2009;Kulikov, 2007). Most observational studies of the Q2DW focus on the summertime Q2DW with the largest amplitudes coming from westward propagating zonal wave numbers W2, W3 and W4 (e.g.…”
Section: Introductionmentioning
confidence: 99%